Performance analysis of wireless power transfer using series-to-series topology - Abdul Shukor, Fairul Azhar; Mohd Nasir, Nur Ashikin; Ahmed Al-Hattami, AAhmed Mohammed Salem; Vaithilingam, Chockalingam Aravind (Institute of Advanced Engineering and Science, 2023)
Wireless power transfer (WPT) is a technology used to transmit power using air as it medium of transfer. The function of the WPT is similar to a transformer. The power provided on the primary side will be transferred through air to the secondary side. The performance of the WPT is crucially depends on the air gap length (